Gratification Reporting and Criminal Exemption: A Substantive Justice Perspective - Hanifah Febriani; M. Junaidi; Devi Luluk Andriani (Faculty of Law, Universitas Lampung, 2025)
This article examines the legal framework of gratification reporting under Articles 12B and 12C of Indonesia’s Anti-Corruption Law through the lens of substantive justice. The law exempts public officials from criminal liability if they report gratification to the Corruption Eradication Commission (KPK) within 30 days, a provision intended to promote transparency but often exploited as a loophole to evade punishment. Using a normative legal method with a statutory approach and case analysis, the research highlights how this mechanism contradicts substantive criminal law and undermines the moral foundation of justice. Drawing on the theories of John Rawls, Amartya Sen, and Ronald Dworkin, the analysis shows that while the provision reflects formal justice, it fails to deliver substantive justice by disproportionately favoring those with legal knowledge and institutional power. The research concludes that Article 12C should be revised to require voluntary reporting before public or law enforcement awareness and within a stricter seven-day window, ensuring greater alignment with both formal and substantive justice.